Ризик-орієнтований підхід до організації системи внутрішнього контролю в готельно-ресторанному бізнесі - Жадан, Тетяна Андріївна; Мелень, Олена Валентинівна (My University, 2020)
У статті розглянуто наявні у науковій економічній літературі трактування понять "внутрішній контроль" та "система внутрішнього контролю", а також особливості застосування традиційного і ризик-орієнтованого підходів до організації системи внутрішнього контролю на підприємстві з урахуванням специфіки діяльності закладів готельно-ресторанного бізнесу. У результаті узагальнення та систематизації визначень поняття "внутрішній контроль" виділено його найістотніші ознаки (мета, завдання, суб’єкти, об’єкти, предмет та етапи процесу внутрішнього контролю), що дало змогу уточнити сутність цієї категорії. На підставі критичного аналізу визначень поняття "система внутрішнього контролю" та підходів до її організації на підприємстві у роботі запропоновано авторське визначення цього поняття з позицій ризик-орієнтованого підходу, що дасть змогу здійснювати своєчасну ідентифікацію й оцінку ризиків, запроваджувати комплекс управлінських заходів, спрямованих на зниження рівня ризиків та наслідків їх впливу до прийнятного.

The main purpose of the study is the further development of theoretical provisions and the development of practical recommendations for the organization of an effective system of internal control in the hotel and restaurant business, the scope of which is characterized by a high degree of uncertainty and risk. In this regard, the main objectives of the study are: generalization and systematization of scientific approaches to defining the essence of the concepts of "internal control" and "internal control system", highlighting their most important features and components, clarifying the content; to carry out the critical analysis of modern approaches to the organization of system of internal control at the enterprise; to substantiate the expediency of organizing the system of internal control on the basis of risk-oriented approach in the hotel and restaurant business. To achieve the goal and solve the tasks in the work used general and special methods of cognition: analysis and synthesis, a systematic approach – to generalize and systematize the definitions of "internal control" and "internal control system", highlighting their most important features and components, clarification content. As a result of generalization and systematization of definitions of the concept of "internal control" its most significant features (purpose, tasks, subjects, objects, subject and stages of the process of internal control) are highlighted, which allowed to clarify the essence of this category, assessment and monitoring of those factors and conditions that negatively affect the implementation of business operations and achieve the goals of the entity, the results of which serve as an information base for the preparation and adoption of sound management decisions aimed at improving the efficiency of the entity. Based on a critical analysis of the definitions of "internal control system" and approaches to its organization in the enterprise, the author's definition of this concept from the standpoint of risk-oriented approach, according to which the internal control system means a set of policies, rules and procedures and reporting, which are implemented by the company's management for the timely identification and assessment of risks and aimed at developing and implementing such management measures that would help reduce the level of risk and the consequences of its impact to acceptable. The paper substantiates the expediency of organizing the internal control system on the basis of risk-oriented approach directly by the management of hotel and restaurant business, which belong to micro and small enterprises, as well as by creating special internal control units for medium and large enterprises.
Risk-oriented approach to the organization of the internal control system in the hotel and restaurant business
Keywords: управління; економічна діяльність; менеджмент; фінансово-господарська діяльність; risk-based approach; internal control; internal control system; restaurant business